Pola Peresepan Antidiabetik Pasien Diabetes Melitus Tipe 2 Rawat Jalan di PKU Muhammadiyah Yogyakarta - Qarriy ‘Aina Urfiyya; Aisyah (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2023)
Background. Diabetes mellitus (DM) is a chronic metabolic disease that continues to increase in number followed by the risk of irrational drug use. This study aims to determine the pattern of antidiabetic prescribing in outpatient type 2 DM patients at PKU Muhammadiyah Yogyakarta. Research Methods: This study used an observational design with retrospective data collection in the medical records of outpatients with type 2 diabetes mellitus for the period October 2021 - March 2022. The sampling technique used a saturated sample of 155 medical records. Data analysis was carried out on antidiabetic therapy based on type and class. The results: Antidiabetic prescriptions include oral antidiabetic monotherapy (22.6%), insulin monotherapy (24.5%), a combination of 2 antidiabetics (31%), a combination of 3 or more oral antidiabetics (3.2%), an antidiabetic-insulin combination (16.1%) and an insulin-insulin combination (2.6%). Conclusion: The most common antidiabetic prescription was insulin monotherapy with a percentage of 31%. The most widely used insulin is novorapid insulin with a percentage of 20%.